"Punk goes pop": a post-semiotic theory of gestural transformation as signifier of style, meaning, and authenticity - Upton, Robert John Peter (2017)
The study of gesture offers a promising extension of semiotic theory. Naomi Cumming (2001), Robert Hatten (2004), and David Lidov (2005), and others have laid the foundations for a critical examination of gestures in music. Their work is, however, married to notated scores of the Western art music tradition: a fact that Giles Hooper (2013) regards as an ironic circling back towards music conceived through implicit analytical-structuralist assumptions.